'It has seemed good to the Holy Spirit and to us' (Acts 15:29): Why Do We Need to be Brothers?. Issue 1 (April 2015) - Lestang, François
Abstract : The call to be brothers, in today's church life as well as in its very beginning, is always a call to conversion and to a discernment. A close look at the questions raised and solved in the Jerusalem Assembly (Acts 15) will allow us to understand not only how the gift of the Holy Spirit unites the church in its diversity of traditions, rites and cultures, but also what kind of behaviour is expected of brothers, then and now.